Systematic review of educational interventions to improve contouring in radiotherapy. (March 2020) - Cacicedo, Jon; Navarro-Martin, Arturo; Gonzalez-Larragan, Susana; De Bari, Berardino; Salem, Ahmed; Dahele, Max
Highlights: The literature on education intervention to improve contouring is limited and heterogenous. On-site, online and blended learning interventions have all been shown to be able to improve contouring. However, impact assessment is almost universally short-term and the effect on clinical practice is unknown. Dice similarity coefficient is the most commonly used end-point, the dosimetric impact effect of improving contouring is rarely analyzed. There is currently no clear indication as to what the best educational methodology/format is. Abstract: Background and purpose: Contouring is a critical step in the radiotherapy process, but there is limited research on how to teach it and no consensus about the best method. We summarize the current evidence regarding improvement of contouring skills. Methods and materials: Comprehensive literature search of the Pubmed-MEDLINE database, EMBASE database and Cochrane Library to identify relevant studies (independently examined by two investigators) that included baseline contouring followed by a re-contouring assessment after an educational intervention. Results: 598 papers were identified. 16 studies met the inclusion criteria representing 370 participants (average number of participants per study of 23; range (4–141). Regarding the teaching methodology, 5/16 used onsite courses, 8/16 online courses, and 2/16 used blended learning. Study quality was heterogenous. There were only 3 randomized studies and only 3 analyzed the dosimetric impact of improving contouring homogeneity. Dice similarity coefficient was the most common evaluation metric (7/16), and in all these studies at least some contours improved significantly post-intervention. The time frame for evaluating the learning effect of the teaching intervention was almost exclusively short-time, with only one study evaluating the long-term utility of the educational program beyond 6 months. Conclusion: The literature on educational interventions designed to improve contouring performance is limited and heterogenous. Onsite, online and blended learning courses have all been shown to be helpful, however, sample sizes are small and impact assessment is almost exclusively short-term and typically does not take into account the effect on treatment planning. The most effective teaching methodology/format is unknown and impact on daily clinical practice is uncertain.